Penerapan Model Pembelajaran Kooperatif Tipe Picture and Picture Untuk Meningkatkan Hasil Belajar Belajar Matematika Siswa Kelas 1 SDN 13 Mataram - Dahlia, Kurnia Ariani; Apriliani, Ni Putu Wangi; Rohyani, Helmy; Arjudin, Arjudin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This research aims to improve student learning outcomes through the Picture and Picture type cooperative learning model in class 1 of SDN 13 Mataram, totaling 19 people in the 2021/2022 academic year. This type of research is collaborative classroom action research. The instrument used in this research is data on student learning outcomes carried out in cycle 1 and cycle 2. The result of this research is an increase in student learning outcomes with scores of 1,285 and 1,530 with the average score in cycle 1 being 67 and cycle 2 being 80. Based on the results of this research, it can be concluded that the picture and picture cooperative learning model can improve the learning outcomes of grade 1 students at SDN 13 Mataram for the 2021/2022 academic year.